O Encontro do Direito Internacional dos Refugiados com o Sul Global: uma análise do “conceito do sul” de refugiado e de sua não aplicação pelas Nações Unidas - Rosa, Marina de Almeida (Universidade do Vale do Rio dos Sinos, 2019)
Protecting individuals who are not safe in their own homes is a practice that has been developed alongside the Western law, imposing different requirements to allow an “outsider” to be protected by another state. In this sense, the international refugee law is based on the Western law and is directed mostly to a selected group, the refugees from the 1951 Convention and the 1967 Additional Protocol. However, the definition of “refugee” contemplated in these treaties turns to a specific individual, who served as a political-ideological argument for the Western powers in the Cold War, and consequently does not support all flows. In finding the Global South, the concept of refugee adopted by the United Nations proved to be insufficient. Thus, in Africa and in Latin America new definitions of “refugee” have been established with the OAU Convention and the Cartagena Declaration, which demonstrate that the causes of refuge in the South are linked to colonialism and to the interventions of the Great Powers. However, even though the concept of refuge originated in the Global South is more protective than the one from the 1951 Convention, it is not applied with the pretension of universality by the United Nations. The present work aims therefore to comprehend the link between the non-application by the United Nations of the southern concept of refuge and the coloniality. Considering that, it seeks to compare the foundations of the refugee definitions from the 1951 Convention, the 1967 Additional Protocol, the OAU Convention and the Cartagena Declaration, as well as the contexts in which they are inserted; besides examining the relation between coloniality and modernity, and the construction of the coloniality of power, of the knowing and being, to comprehend how the southern epistemologies, allied to the TWAIL, can fundament the enlargement of the concept of refugee. Furthermore, it seeks to recognize the refugee as the “other”, an “outsider”, so that it can be known by the decolonial lenses, and how this condition relates to the refusal of applying the concepts of the OAU Convention and the Cartagena Declaration by the United Nations with universal pretensions. It also examines the link between the non-application of the southern concept of refugee and the classic bases of international law, with the manipulation of the language of law and with “who speaks for the refugee”, as well as the centralization of the possibility of extending the concept of refugee in the UNHCR. With the application of the dialectical, monographic, historical and comparative methods, it will be verified that the non-application of the concept of refugee, which considers those who flee from generalized violence, aggression, domination or foreign occupation, internal conflicts, massive violation of human rights or from other circumstances that disturb public order, is related to the locus in which this definition emerges, the Global South, since its non-application reaffirms the Eurocentric ethos of international law, besides appointing to the characteristics of the coloniality of the knowing and being, and demonstrating the relation between the power and knowledge, restricting the definition of refugee to an international organism that suffers with the influences of hegemonic states.

La protección de personas que no están seguras en sus domicilios es práctica desarrollada del derecho occidental, que impone diferentes requisitos para permitir que un “elemento exterior” sea amparado por otro Estado. En ese sentido, el derecho internacional de los refugiados se fundamenta en el derecho occidental y se direcciona, predominantemente, a un selecto grupo, los refugiados de la Convención de 1951 y del Protocolo sobre el Estatuto de 1967. Sin embargo, la definición de “refugiado” contemplada por esos tratados se dirige a un individuo específico, lo cual servirá de argumento político-ideológico para las potencias Occidentales en la Guerra Fría, y, consecuentemente, no ampara todos los flujos. Cuando ha encontrado el Sur Global, el concepto de refugiado que la ONU adopta se ha mostrado insuficiente. Así, en África y en América Latina han sido instituidas otras definiciones de “refugiado” con la Convención de la OUA y la Declaración de Cartagena, y que han demostrado que las causas del refugio en el Sur son vinculadas al colonialismo y a las intervenciones de las grandes potencias occidentales. Ocurre que, aunque el concepto de refugiado originado en el Sur global garantice más los derechos de los refugiados y proteja un número más elevado de personas que la Convención de 1951, él no es aplicado con pretensiones de universalidad por la ONU. El presente trabajo tiene, por lo tanto, por objetivo comprender el vínculo existente entre la no aplicación, por la ONU, del concepto del Sur de refugiado y la colonialidad. Por ende, busca comparar las fundamentaciones de las definiciones de refugiado de la Convención de 1951, de su Protocolo de 1967, de la Convención de la OUA y de la Declaración de Cartagena, así como los contextos en los cuales están insertado; además de examinar la relación entre la colonialidad y la modernidad, y la construcción de la colonialidad del poder, del saber y del ser, para comprender como las epistemologías del Sur, añadidas a la TWAIL, suelen fundamentar la ampliación de la definición de refugiado. Además, procura reconocer el refugiado como el “Otro”, un outsider, para que se pueda conocerlo bajo la perspectiva decolonial, y como dicha condición está relacionada a la no aplicación de los conceptos de la Convención de la OUA y de la Declaración de Cartagena por la ONU con pretensiones universales. Se examina el vínculo entre la no aplicación del concepto del Sur de refugiado con las bases clásicas del derecho internacional, con la manipulación del lenguaje de derecho y con “quien habla por el refugiado”, así como con la centralidad de la posibilidad de la ampliación del concepto de refugiado en el ACNUR. Por medio de la aplicación de los métodos dialéctico, monográfico, histórico y comparativo, se va a verificar que la no aplicación del concepto de refugiado que lleva en cuenta aquellos que han huido de la violencia generalizada, de la agresión, dominación u ocupación extranjera, de los conflictos internos, de la violación masiva de los derechos humanos u otras circunstancias que hayan perturbado gravemente el orden público, se relaciona con el locus en lo cual esa definición se ha originado, el Sur global, porque su no aplicación reafirma el ethos eurocéntrico del derecho internacional, además de apuntar para las características de la colonialidad del saber y del ser, y demostrar la relación entre poder y conocimiento, delimitando la definición de refugiado a un organismo internacional que sufre con las influencias de los Estados hegemónicos.
Keywords: Direito internacional dos refugiados; Epistemologias do Sul; Decolonialismo; TWAIL; Colonialidade; International refugee law; Epistemologies of the South; Decolonialism; TWAIL; Coloniality; Derecho internacional de los refugiados; Epistemologías del Sur; Decolonialismo; TWAIL; Colonialidad; ACCNPQ::Ciências Sociais Aplicadas::Direito